A STUDY ON CLINICAL PROFILE AND OUTCOME OF RODENTICIDE POISONING IN SOUTH INDIA: A CROSS-SECTIONAL STUDY - MURUGESAN, MALARVIZHI; NATARAJAN, RADHAKRISHNAN; PANDIAN, PRASANNA DEVI; SHANMUGAM, JEEVITHAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study were to study the sociodemographic profile, clinical features, and clinical outcome of patients admitted with rat killer poison in a tertiary care hospital in South India. Methods: A cross-sectional study was conducted among those who have been admitted with rodenticide poisoning in a tertiary care center in South India. Prior Institutional Ethical committee Permission and written informed consent were obtained. Data on sociodemographic profile were elicited. The clinical course of all those who were enrolled in the study was closely followed and monitored. All the necessary blood parameters were done on every alternate day after the admission blood investigations. The data were entered into Microsoft excel and were analyzed using PSPP software. The difference in mean blood parameters between survivors and non survivors was compared. Results: The consumption of rodenticide poisoning was higher among females (59%). Majority (58%) were married. Vomiting was present in nearly two-third of the study population and abdominal pain in 21%. Dose ingested and time of reporting to hospital were high among non-survivors. Mean bilirubin, serum glutamic-oxaloacetic transaminase, serum glutamic pyruvic transaminase, and International normalized ratio were higher among non-survivors compared to survivors at all the days measured. Conclusions: Monitoring of liver parameters plays a key role in assessing the prognosis of the patient and also in treating them.